2020
DOI: 10.2298/saj2001039v
|View full text |Cite
|
Sign up to set email alerts
|

Classification of asteroid families with artificial neural networks

Abstract: This paper describes an artificial neural network for classification of asteroids into families. The data used for artificial neural network training and testing were obtained by the Hierarchical Clustering Method (HCM). We have shown that an artificial neural networks can be used as a validation method for the HCM on families with a large number of members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In this region, however, even the traditional HCM is still applicable due to the significantly smaller number of objects than the main belt's low-inclination part. Vujičić et al (2020) explored the possibility of using an artificial neural network (ANN) for the classification of asteroids into families. The obtained results showed that the ANNbased algorithm performs somewhat better than the clustering algorithms tested by .…”
Section: Machine Learning-based Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In this region, however, even the traditional HCM is still applicable due to the significantly smaller number of objects than the main belt's low-inclination part. Vujičić et al (2020) explored the possibility of using an artificial neural network (ANN) for the classification of asteroids into families. The obtained results showed that the ANNbased algorithm performs somewhat better than the clustering algorithms tested by .…”
Section: Machine Learning-based Methodologymentioning
confidence: 99%
“…A possible solution to deal with a large amount of data for the purpose of classification of asteroids into families could be a multi-step methodology proposed by Milani et al (2014, see also Milani et al 2016. Alternatively, the problem could be treated by employing machine learningbased tools, which can be used either to identify new asteroid families Vujičić et al 2020), or to attach new members to known families (Carruba et al 2020a).…”
Section: Recent Advances In Asteroid Family Identificationmentioning
confidence: 99%